Estimation of Some Antioxidant Factors in Postmenopausal Iraqi Women with Hypertension - Jassim, Abeer Mohammed; Hussain, Zainab Khidhair (Iraqi Journal of Science, 2024)
Postmenopausal women with hypertension may be linked with cardiovascular risk factors like visceral obesity. Changes in antioxidant levels  and lipid profile are considered risk factors concerning heart disease that arises during postmenopausal. Ninety Iraqi women aged between 53-70 years, sixty women with postmenopausal hypertension, and thirty healthy postmenopausal women were selected  as control for this study. Blood samples were taken to measure some antioxidants through enzyme-linked immune sorbent assay (ELISA) and lipid profile by enzymatic technique. Results  showed that the mean of catalase levels was significantly lower in patients (257.62±6.99) compared towith the control group (499.30±13.08). Glutathione results were significantly lower in patients (10.99±0.26) compared with the healthy control (39.32±2.03). Cholesterol levels were significantly higher in patients (236.09±1.91), while lower levels were observed in the control group (172.67±4.92). Triglyceride levels were significantly higher both in patients (182.10±2.68) and the healthy group (145.92±5.85). HDL levels were significantly lower in patients (29.91±0.37) compared with the control group (43.02±1.38). VLDL levels were significantly higher in patients (36.49±0.54) compared with the control (29.16±1.17). LDL levels were significantly higher in patients (169.74±2.20) than in the control group (1 00.48±5.41). It can be concluded from the results that antioxidant levels decreased in postmenopausal women than in the control group. Elevation in lipid profile of postmenopausal women was observed compared with the control group.